Financialisation and rental housing: A case study of Berlin - Clementine Davies (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2021)
This paper seeks to understand the extent financialisation has had an impact on the rental housing market in Berlin. Specifically, it focuses on the financialisation of non-financial rental housing companies. The financial statements of five large, publicly listed, commercial rental housing companies in Berlin are examined for three operationalisations of financialisation: as a means of accumulation, as a mode of corporate governance, and as the prioritisation of short-term perspectives. Findings show no trends of firms increasingly relying on financial instruments for profit but did show increased shareholder orientation and short termism. Implications for the supply, price and quality of rental housing in Berlin are discussed.
Keywords: G3; G32; L2; N2; R21; R31; 330; financialisation; homeownership; firm ownership structure; rental housing; rental market; Berlin